ABOUT THE WORD "KHUD" AND ITS MORPHOLOGICAL SIGNS IN NAVOYI'S EPIC "SADDI ISKANDARI" (Scientific journal of the Fergana State University, 2024)
This article talks about the word “khud”, its morphological features and function in the sentence of Alisher Navoi’s epic “Saddi Iskandari”. When using the word “khud” in the categories of pronouns and adjectives, its lexical-semantic features are presented, based on comments in Persian-Tajik dictionaries, and the lexical meanings of Persian words in the annotated dictionary of Navoi’s works. We are also talking about the fact that the word “khud” in the Persian language refers only to a group of pronouns, and also takes possessive suffixes in a sentence. The lexical and semantic features of the Persian words mentioned in the article are explained.